50.2: Invited Paper: Improving lifetime and output current of organic‐based gas sensor for applications in breath detection. (4th October 2019) - Yu, Shang-Yu; Zan, Hsiao-Wen; Chen, Chang-Chiang; Meng, Hsin-Fei; Lu, Chia-Jung
Abstract : We exploited the stability of Donor‐Acceptor polymer on the cylindrical nanopores structure to realize the sensors with a high sensitivity and stability. Then, we propose a double active layer (DL) strategy that exploits an ultra‐thin layer of Poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) to serve as a work function buffer to enhance the operational current. The DL sensor exhibits a sustainable enhanced operational current of microampere level and a stable sensing response even with the presence of P3HT layer. This effect is carefully examined with different aspects, including vertical composition profile of DL configuration, lifetime testing on different sensing layer, morphological analysis, and the versatility of the DL strategy. Finally, we utilize the DL sensor to conduct a tracing of BA concentration in two HD patients before and after HD, and correlate it with the blood urea nitrogen (BUN) levels. A good correlation coefficient of 0.96 is achieved.